Factors that effect business continuity and disaster recovery plan in the ADNOC onshore in the United Arab Emirates - Arif Faraj Awadh Abdulla, Alseiari (2022)
The oil and gas industry is recognized as the leading industry around the world because of the importance of oil and gas for every human being around the globe. The oil and industry involves almost every other industry, as without engines, life could be very difficult. The Abu Dhabi National Oil Company (ADNOC) is one of the world's leading companies in the energy sector. Its operations extend to the entire hydrocarbon value chain, with operations ranging from exploration, production, storage, refining and distribution to the development of a wide range of petrochemical products. The business continuity and disaster recovery plan focus on reducing the risks that cause problems in the normal operations of the organization. There are several social and economic problems that affect the profitability of the oil and gas industry globally, for the current research, the main problem is investigating factors that affect oil and gas business continuity is necessary for this industry’s sustainability. This study was formulated for the purpose of evaluating the business continuity and disaster recovery plan of ADNOC Onshore in the United Arab Emirates. The literature background was provided for the topic's variables in order to provide a theoretical background to the research framework. The data collection process for this research began with the preparation of a questionnaire. The questionnaires were distributed randomly to ADNOC Onshore Companies in Abu Dhabi to the research location. The research used a well-known statistical program that is often used in quantitative methods. The program, the Statistical Package for Social Sciences (SPSS) version 23, was used to analyze the data collected. The study found that project initiation, risk assessment, business affect analysis, mitigation strategy development, plan development, plan testing, auditing, and maintenance, and training affect the evaluation of business continuity and disaster recovery plan by ADNOC Onshore. As an implication of the study, this study reveals that ADNOC managers must pay more attention to business continuity because, the oil and gas sector is not a stable sector, it can drop immediately with no notice by reasons like wars, so by oil and gas companies must be having solid and vital business continuity and disaster recovery plans for such incidents.